2023
DOI: 10.1021/acsomega.2c07292
|View full text |Cite
|
Sign up to set email alerts
|

Biowaste Eggshell Membranes for Bio-triboelectric Nanogenerators and Smart Sensors

Abstract: In this study, we used a simple and cost-effective method to fabricate triboelectric nanogenerators (TENGs) based on biowaste eggshell membranes (EMs). We prepared stretchable electrodes with various types of EMs (hen, duck, goose, and ostrich) and employed them as positive friction materials for bio-TENGs. A comparison of the electrical properties of the hen, duck, goose, and ostrich EMs revealed that the output voltage of the ostrich EM could reach up to 300 V, due to its abundant functional groups, natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…In particular, the plasma−treated PVDF fabric had a voltage output stability of 45% and a current output stability of 77%, resulting in the highest energy harvesting performance stability among the tested samples [57]. Lin et al [58] demonstrated a simple and cost-effective method for fabricating TENG devices using eggshell membranes (EMs). Before coating a metallic electrode, the PDMS was treated by using a commercial N 2 atmospheric plasma treatment (Harrick Plasma, PDC-32G) for 0, 2, and 12 h under an atmospheric environment to form a hydrophilic PDMS surface.…”
Section: Plasma Surface Modification Of Triboelectric Polymer Using P...mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the plasma−treated PVDF fabric had a voltage output stability of 45% and a current output stability of 77%, resulting in the highest energy harvesting performance stability among the tested samples [57]. Lin et al [58] demonstrated a simple and cost-effective method for fabricating TENG devices using eggshell membranes (EMs). Before coating a metallic electrode, the PDMS was treated by using a commercial N 2 atmospheric plasma treatment (Harrick Plasma, PDC-32G) for 0, 2, and 12 h under an atmospheric environment to form a hydrophilic PDMS surface.…”
Section: Plasma Surface Modification Of Triboelectric Polymer Using P...mentioning
confidence: 99%
“…50 nm and 1.34 Ω, respectively [58]. Figure 35c displays the amounts of charge transferred for the various types of EMs.…”
Section: Plasma Surface Modification Of Triboelectric Polymer Using P...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, waste natural fibers such as eggshell membranes 75 and onion membranes 76 can also be used for the preparation of W-TENGs. Yan et al 77 used a carbonized eggshell membrane (ESM) as the positive friction material with an output voltage of 156.12 V. Compared with the non-carbonized ESM, the output voltage is increased by about 198%.…”
Section: Friction Layer and Electrode Materials Of The W-tengmentioning
confidence: 99%
“…Among them, ostrich EM has the advantages of rich functional groups, natural fiber structure, high surface roughness, high surface charge, and a high dielectric constant. [49] EM-TENG not only shows excellent electrical performance of an outputting voltage up to 330 V but can also be used as a smart sensor to monitor body movement. [50][51][52][53][54] In this study, the EM-TENG was attached to the elbow, wrist, and knee joints, which allowed to monitor the magnitude of change during different articular motions.…”
Section: Introductionmentioning
confidence: 99%